Turbulent Generation of Magnetic Switchbacks in the Alfvénic Solar Wind - Shoda, Munehito; Chandran, Benjamin D. G.; Cranmer, Steven R. (The Astrophysical journal, 2021)
One of the most important early results from the Parker Solar Probe (PSP) is the ubiquitous presence of magnetic switchbacks, whose origin is under debate. Using a three-dimensional direct numerical simulation of the equations of compressible magnetohydrodynamics from the corona to 40 solar radii, we investigate whether magnetic switchbacks emerge from granulation-driven Alfvén waves and turbulence in the solar wind. The simulated solar wind is an Alfvénic slow-solar-wind stream with a radial profile consistent with various observations, including observations from PSP. As a natural consequence of Alfvén-wave turbulence, the simulation reproduced magnetic switchbacks with many of the same properties as observed switchbacks, including Alfvénic v – b correlation, spherical polarization (low magnetic compressibility), and a volume filling fraction that increases with radial distance. The analysis of propagation speed and scale length shows that the magnetic switchbacks are large-amplitude (nonlinear) Alfvén waves with discontinuities in the magnetic-field direction. We directly compare our simulation with observations using a virtual flyby of PSP in our simulation domain. We conclude that at least some of the switchbacks observed by PSP are a natural consequence of the growth in amplitude of spherically polarized Alfvén waves as they propagate away from the Sun.